1993
DOI: 10.2307/2390129
|View full text |Cite
|
Sign up to set email alerts
|

Differential Atresia of Ovarian Follicles and its Effect on the Clutch Size of Two Populations of the Viviparous Lizard Sceloporus mucronatus

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. British Ecological Society is collaborating with JSTOR to digitize, preserve and extend access to Functional Ecology. Summary 1. The phenomenon of follicular atresia, defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 17 publications
(18 reference statements)
1
8
0
1
Order By: Relevance
“…Mendez-de la Cruz et al (1993) also found no evidence of embryonic death in utero in Sceloporus mucronatus. In contrast atresia of vitellogenic follicles is commonly found in lizards and is often extensive.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Mendez-de la Cruz et al (1993) also found no evidence of embryonic death in utero in Sceloporus mucronatus. In contrast atresia of vitellogenic follicles is commonly found in lizards and is often extensive.…”
Section: Discussionmentioning
confidence: 90%
“…Guillette and Casas-Andreu (1987) reported 29% atresia in Barisia i. imbricata, with possibly as much as 40% in B. i. ciliaris. Mendez-de la Cruz et al (1993) demonstrated that atresia rates are not necessarily fixed and may vary considerably. Size specific rates in Sceloporus mucronatus were 17.0% and 54.6% for a lowland and montane population respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did note that, as described in species with megalecithal eggs, granulosa cells in atretic vitellogenic follicles of M. brachypoda move to the ooplasm, where they form phagocytes which ingest and digest the yolk bodies (for review, see Saidapur, 1978). Atretic follicles play an important role in limiting the number of eggs produced during each reproductive cycle, can also be a significant element in regulating steroid production, and are a means to destroy defective follicles or eggs (Saidapur, 1978; Mé ndez de la Cruz et al, 1993). For example, we observed several polyovular follicles, also described as multioocytic follicles, in which the ovarian follicle houses more than one oocyte.…”
Section: Discussionmentioning
confidence: 99%
“…In preovulatory ovaries, atresia provides a mechanism for controlling the final number of follicles that ovulate during the process of follicular selection (Jones et al, 1982;Andreuccetti et al, 1990). Jones and Swain (2000) suggested that there are two possible mechanisms regulating clutch size in Squamata, either recruitment (Sinervo and Licht, 1991) or a subsequent atresia (Méndez de la Cruz et al, 1993) and in viviparous species a third mechanisms exists (loss of developing embryos; Blackburn, 1998). Follicular atresia was very high in growing follicles and minimal in preovulatory follicles in Mabuya mabouya.…”
Section: Follicular Atresiamentioning
confidence: 99%